TO017CLINICAL CHARACTERISTICS AND INDEPENDENT PREDICTORS OF CHECK POINT INHIBITORS-ASSOCIATED AKI: WHAT DO WE KNOW?. (6th June 2020) - Bolufer, Mónica; Garcia Carro, Clara; Bury, Roxana; Muñoz, Eva; Felip, Enriqueta; Gabaldon, Alejandra; Carreras, Maria Jose; Seron Micas, Daniel; Soler, María José
Abstract: Background and Aims: Checkpoint inhibitors (CPI) are used to treat solid organ malignancies. CPI–associated acute renal injury (AKI) is an adverse effect of these therapies and its incidence is 13-29%. Clinical data on this complication is scarce. The aim of our study is to define clinical characteristics and risk factors of CPI-associated AKI. Method: Clinical and demographic data of all patients receiving immunotherapy between March 2018 and May 2019 at our center were evaluated. Patients were divided into two groups depending on the development of AKI during the study period. AKI was defined according to AKIN classification. We compared clinical and demographic characteristics between these two groups and patients who developed mild AKI and severe AKI. Results: During the study period, 821 patients received CPIs. Mean age 62.03±12.06 years and 486(59.2%) men. Malignancies were lung in 249 (30.3%), urogenital tract in 168 (20.5%), melanoma in 89 (10.8%) and others in 315 patients (38.4%). 446(54.3%) patients received anti-PD1, 230(28%) anti-PDL1, 13 (1.6%) anti-CTLA4, 36 (4.4%) received other drug and 96(11.7%) were treated with both anti-CTLA4 and anti-PD1 or anti.PDL1. Baseline creatinine was 0.85±0.30 mg/dL and 188 (22.9%) patients presented creatinine>1 mg/dL before starting CPI. 125 patients (15.2%) developed AKI during the study period, 85(68%) men and mean age 65.1±10.7 years. Baseline creatinine of these patients 0.97±0.45 mg/dL and 44 (35.2%) presented basal creatinine>1mg/dL. Mean creatinine at the diagnosis of AKI 2.27±1.34 mg/dL and two patients required haemodialysis. Leukocyturia was present in 21 patients(16.8%) and haematuria in 12 (9.6%). 5 patients presented AKI secondary to obstructive uropathy. Mean time from CPI initiation to AKI was 5.6±5.8 months. Of those 125 patients, 23 (18.4%) were referred to Nephrology and 9 (7.2%) underwent kidney biopsy. 1 patient presented endocapillar proliferative non-CPI related glomerulonephritis and 8 (6.4%) acute tubule-interstitial nephritis (ATIN). 23 (18.4%) patients were treated with corticosteroids. Mean creatinine at 6 months after AKI was 1.04±0.34 mg/dL (data from 45 patients) and 40 patients (data from 45 patients) showed complete recovery of kidney function at 6 months. Patients who developed a severe AKI stage 2 or 3 were more frequently women (41.8% vs 24.3%, p=0.03), had lower basal creatinine (0.86±0.25 vs 1.06±0.54 mg/dL, p=0.0130), showed and increased latency from CPI initiation to AKI (6.9±6 vs 4.5±5.5 months, p=0.0267) and presented worse recovery of kidney function at 6 months than patients with AKI stage 1(creatinine 6 months 1.18±0.40 mg/dL, p=0.0398 and complete recovery of kidney function at 6 months 70.5% vs 93.3%, p=0.0353). There was no association between the severity of AKI and type of CPI and type of malignance. When comparing patients who developed AKI with patients whit patient who did not, patients with AKI were older (65.1±10.7 vs 62.03±12.06 years old, p=0.0017), more frequently men (68% vs 57.9%), p=0.0296) and presented higher baseline creatinine (0.97±0.45 vs 0.85±0.30 mg/dL, p<0.0001), as well as more frequently a baseline creatinine > 1 mg/dL (35.2% vs 20.7%, p=0.0004). Type of CPI and type of malignance were not associated with the presence of AKI. Older age (OR 1.020, CI 95% 1.002-1.038) and baseline creatinine (OR 3.293, CI 95% 1.678-6.461) were identified as independent predictors of AKI development in our CPI treated patients Conclusion: CPI-associated AKI incidence in our centre is 15.2%. Of them, 44% developed severe AKI. Only 18.4% were referred to a nephrologist and kidney biopsy performed in 7.2%. ATIN was the most common diagnosis. 18.4% received corticosteroids. Older age and higher baseline creatinine were identified as independent predictors for AKI development in patients with cancer CPI-treated. Patients developing a severe AKI showed worse kidney function at 6 months.